1994
DOI: 10.1523/jneurosci.14-07-04095.1994
|View full text |Cite
|
Sign up to set email alerts
|

Distributed processing of pain and vibration by the human brain

Abstract: Pain is a diverse sensory and emotional experience that likely involves activation of numerous regions of the brain. Yet, many of these areas are also implicated in the processing of nonpainful somatosensory information. In order to better characterize the processing of pain within the human brain, activation produced by noxious stimuli was compared with that produced by robust innocuous stimuli. Painful heat (47-48 degrees C), nonpainful vibratory (110 Hz), and neutral control (34 degrees C) stimuli were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
353
1
8

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 738 publications
(418 citation statements)
references
References 79 publications
51
353
1
8
Order By: Relevance
“…Acute phasic noxious stimulation has been used in most of these studies. Apart from some inconsistencies, there is a general consensus that such stimuli activate the anterior cingulate cortex (ACC) and the mid-/anterior insula of the medial pain system as well as the primary-and secondary somatosensory cortices (S1 and S2) of the lateral pain system Talbot et al, 1991;Casey et al, 1994Casey et al, , 1996Coghill et al, 1994;Apkarian, 1995;Davis et al, 1995Davis et al, , 1997Hsieh, 1995;Vogt et al, 1996). These ®ndings support the hypothesis that the experience of pain is processed in a parallel interactive and distributed fashion.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Acute phasic noxious stimulation has been used in most of these studies. Apart from some inconsistencies, there is a general consensus that such stimuli activate the anterior cingulate cortex (ACC) and the mid-/anterior insula of the medial pain system as well as the primary-and secondary somatosensory cortices (S1 and S2) of the lateral pain system Talbot et al, 1991;Casey et al, 1994Casey et al, , 1996Coghill et al, 1994;Apkarian, 1995;Davis et al, 1995Davis et al, , 1997Hsieh, 1995;Vogt et al, 1996). These ®ndings support the hypothesis that the experience of pain is processed in a parallel interactive and distributed fashion.…”
Section: Introductionmentioning
confidence: 79%
“…First, the contrasts Allodynia -Rest, Allodynia -Contralateral touch, Rest -Allodynia, Contralateral touch -Allodynia and Contralateral touch -Rest were analyzed, using a multisubject with replications design (3 conditions, 5 blocks (subjects)). The rCBF increases were investigated in a pre-de®ned pain network based on previous functional imaging studies of pain (Di Piero et al, 1991, 1994Jones et al, 1991;Talbot et al, 1991;Apkarian et al, 1992Apkarian et al, , 1995Casey et al, 1994Casey et al, , 1996Coghill et al, 1994;Davis et al, 1995;Drevets et al, 1995;Hsieh, 1995;Hsieh et al, 1995a,b;Iadarola et al, 1995;Craig et al, 1996;Vogt et al, 1996). The pain network included the contralateral S1 and, bilaterally, the thalamus, S2, insula, ACC and the periaqueductal gray (PAG).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of limbic structures in nociceptive processing and of structures associated with pain modulation is expected because the limbic system has long been believed to play an important role in neural mechanisms related to the affective-motivational dimension of pain (Melzack and Casey, 1967;Hylden et al, 1986;Geisler et al, 1994;Chapman, 1996;Willis and Westlund, 1997). Recent studies using positron emission tomography also report significant increases in regional blood flow in limbic forebrain structures during acute or chronic pain perception in humans (Talbot et al, 1991;Jones et al, 1991;Casey et al, 1994Casey et al, ,1996Coghill et al, 1994;Hsieh et al, 1995Hsieh et al, ,1996Vogt et al, 1996). Anatomical studies have shown that limbic structures receive spino-reticulo-thalamic input via connections from the thalamic medialintralaminar nuclei and thalamic reticular nucleus Robertson and Kaitz, 1981).…”
Section: Changes In Rcbf In Limbic Structures After Cci-several Forebmentioning
confidence: 99%
“…Substantial evidence shows that increases in regional cerebral blood flow (rCBF) are tightly and positively coupled to increases in synaptic glucose metabolism and electrical activity (Sokoloff, 1978;Sokoloff, 1981;Mraovitch et al, 1992;Malonek and Grinvald, 1996). Studies in humans using positron emission tomography (PET) have revealed unique patterns of changes in rCBF that are associated with the perception of pain Talbot et al, 1991;Casey et al, 1994;Coghill et al, 1994). Such studies provide insights into the function of the pain network as a whole; information that was previously unattainable from clinical data or individual pharmacological, stimulation, lesion or electrophysiological experiments.…”
Section: Introductionmentioning
confidence: 99%